Experimental Evaluation of Faecal Escherichia coli and Hepatitis E Virus as Biological Indicators of Contacts Between Domestic Pigs and Eurasian Wild Boar. Issue 2 (19th July 2015) - Barth, S.; Geue, L.; Hinsching, A.; Jenckel, M.; Schlosser, J.; Eiden, M.; Pietschmann, J.; Menge, C.; Beer, M.; Groschup, M.; Jori, F.; Etter, E.; et al.
Summary: Domestic pigs and Eurasian wild boar ( Sus scrofa ) share several important viral and bacterial pathogens. Therefore, direct and indirect contacts between domestic pigs and wild boar present a risk of pathogen spillover and can lead to long‐term perpetuation of infection. Biological indicators could be a powerful tool to understand and characterize contacts between wild boar and domestic pigs. Here, faecal Escherichia coli and Hepatitis E virus (HEV) were explored as potential biological indicators under experimental conditions. The data gained in our pilot study suggest that faecal E. coli can be used as biological indicator of contact between wild boar and domestic pig. For HEV, faecal transmission was also confirmed. However, molecular studies on full‐genome basis did not reveal markers that would allow tracing of transmission direction. Based on these promising results, future field studies will especially target the practicability of E. coli microbiome molecular typing as surrogate of contacts at the wildlife–livestock interface.